Manejo de plantas daninhas dicotiledôneas na cultura da soja (Glycine max L, Merr.) - Silva, Leandro (2011)
Broadleaf weeds, always have been and remain the point of view of weed management, a major challenge for technicians and farmers who work with soybean. This study aims to seek alternative management for these species within a production system using RR soybeans. The experiment was implemented in the county of Não-Me-Toque - RS in the agricultural year 2009/2010 was conducted in randomized block design in a sub-plot with four replications subdivided, where they were tested five winter cover plots, six managements chemical presowing soybean subplots and three managements chemical postemergence soybean in sub-subplots. None of the treatments proved to be phytotoxic to soybean plants. The sequential applications post-emergence showed up with a trend of reduction of plant height, which did not impact negatively on the productivity of the plots. In treatments with coverage of oats, wheat or ryegrass, any combination of managements in pré and post-sowing returned horseweed control values above 90%. In general, the best treatments for control of milk and string-of-rape were the combinations of glyphosate and glyphosate + diclosulam or sulfentrazone in pre-planting soybeans. The best treatment for management of wild radish was obtained in situations where the active ingredient metsulfuron-methyl was used. When soybeans are planted in fallow areas, productivity is on average 8% lower than when sown in areas with coverage of oats or wheat. In general, treatments that returned the highest yields were implanted using glyphosate or glyphosate + + diclosulam sulfentrazone in preplanting soybeans.